Agro-dealers and end-user demand ('pull')-driven seed system innovation in Eastern Kenya: Realities today; opportunities tomorrow - CGIAR Research Program on Maize (2021)
A steady supply of quality stress-tolerant seed is necessary, but not sufficient to achieve higher varietal turnover rates. The key to transformation lies in addressing distribution challenges. Research confirmed agro-dealers' and seed companies' overarching supply-push orientation, characterized by limited innovation and risk taking, pointing to the major opportunity of ender-user-driven marketing. The agro-dealer's role in facilitating varietal turnover could be much greater and beneficial to the farmer. This multi-year research generated growing donor and investor interest in seed marketing research.